2021
DOI: 10.1097/md.0000000000027760
|View full text |Cite
|
Sign up to set email alerts
|

Demarcation of early esophageal squamous cell carcinoma during endoscopic submucosal dissection

Abstract: Lugol's iodine staining (LIS) and narrow-band imaging (NBI) are currently the most common methods applied in demarcating early esophageal squamous cell carcinoma (EESCCs) during endoscopic submucosal dissection. The purpose of the present study was to investigate the effects on clinical outcomes in comparison between LIS and NBI for the demarcation of EESCCs during endoscopic submucosal dissection. This was a single-center, retrospective, cohort study. A total of 172 patients were involved. 109 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(71 reference statements)
0
2
0
1
Order By: Relevance
“…A prospective comparative study confirmed the higher specificity of NBI staining in tumor detection [9]. Two retrospective studies investigating the appropriate staining method for delineating the lateral extent of the tumor before endoscopic resection showed no difference between NBI and Lugol staining [10, 11]. Due to the available data, the lateral resection margins should be determined using virtual chromoendoscopy or Lugol staining before endoscopic resection of an esophageal SCC.…”
Section: Endoscopic Assessment Of Tumor Extent Prior To Endoscopic Re...mentioning
confidence: 99%
“…A prospective comparative study confirmed the higher specificity of NBI staining in tumor detection [9]. Two retrospective studies investigating the appropriate staining method for delineating the lateral extent of the tumor before endoscopic resection showed no difference between NBI and Lugol staining [10, 11]. Due to the available data, the lateral resection margins should be determined using virtual chromoendoscopy or Lugol staining before endoscopic resection of an esophageal SCC.…”
Section: Endoscopic Assessment Of Tumor Extent Prior To Endoscopic Re...mentioning
confidence: 99%
“…2 Otros usos de lugol incluyen el marcaje durante la disección submucosa endoscópica en pacientes con carcinoma esofágico en estadio precoz y en el tratamiento preoperatorio de quienes padecen enfermedad de Graves. 2,3 A pesar de su uso generalizado, se han reportado casos excepcionales de reacciones alérgicas y hasta la fecha no se ha descrito su potencial alergenicidad. De acuerdo con la bibliografía disponible al momento, exponemos el segundo caso de reacción alérgica a lugol.…”
Section: Antecedentesunclassified
“…A recent meta-analysis revealed no significant difference in diagnostic sensitivity between the two methods (88% versus 92%); it also revealed that NBI has a significantly higher specificity than Lugol's iodine chromoendoscopy (88% versus 82%) [7]. Furthermore, several observational studies reported no significant difference in complete resection rate between the two methods [8,9].…”
Section: Lugol's Iodine Chromoendoscopymentioning
confidence: 99%